The Norton introduction to literature - Mays, Kelly J. (W. W. Norton & Company, 2016)
"The most trusted guide for helping students read critically and write carefully. The Norton Introduction to Literature presents an engaging, balanced selection of literature to suit any course. Offering a thorough treatment of historical and critical context, the most comprehensive media package available, and a rich suite of tools to encourage close reading and thoughtful writing, the Twelfth Edition is unparalleled in its guidance of understanding, analyzing, and writing about literature."--Provided by publisher